S13.2 Should enteric infections in MSM always be treated?. (14th July 2019) - Pakianathan, Mark
Abstract : Sexual transmitted enteric infections (STEIs) have been well recognised in gay, bisexual and other men who have sex with men (GBMSM) for over three decades. This presentation will initially provide an overview of the range of enteric pathogens with propensity for sexual transmission in this population. There has been a recent increase in the numbers of outbreaks of enteric infections reported affecting this population in particular with shigella species and Hepatitis A. These have occurred across borders reflecting internationally mobile GBMSM networks. Recently, multi-drug antimicrobial resistance (AMR) in strains of Shigella sonnei circulating amongst GBMSM in England and USA have been identified challenging standard treatment approaches. The epidemiology of some of these outbreaks, the emergence of AMR and public health responses will be discussed. Outbreaks of shigella have been linked to HIV status and parallel epidemics of gonorrhoea (also linked with AMR), syphilis and Lymphogranuloma venereumin this population of GBMSM. Whilst the majority of shigella infections in GBMSM will be self-limiting, contextual and clinical factors may lower the threshold for antimicrobial treatment. The presentation highlights some of these challenges and dilemmas in clinical management particularly in the face of co-infection with STIs, the emergence of AMR and syndemic health inequalities such as problematic chemsex (use of psychoactive substances with sex). The presentation will conclude with research gaps, implications for policy on STEIs and emphasize the need for partnership working across public health, microbiology and relevant frontline clinical services. The need for management approaches that are holistic and consider wider syndemic health needs when managing patients will also be highlighted. Disclosure: No significant relationships.